One-pot synthesis of Fe2O3/C by urea combustion method as an efficient electrocatalyst for oxygen evolution reaction. (28th January 2019) - Zhang, Zejie; Zhou, Debi; Bao, Xinjun; Huang, Gonghong; Huang, Boyun
Abstract: The hematite type Fe2 O3 /C catalyst for oxygen evolution reaction (OER) was prepared using a facile urea combustion method. The Fe2 O3 /C electrode showed excellent electrocatalytic ability towards OER in alkaline medium. The phase and morphology of the product were characterized by X-ray diffraction (XRD) and scanning electron microscope (SEM). The sintering temperature is 600 °C, and the calcination time is 3 h, which is the best preparation process condition. The particles were irregular spherical with the size of 10–30 nm and dispersed uniformly. The current density of the Fe2 O3 /C electrode was 147 mA cm −2 at 0.6 V (vs. HgO/Hg) in 6 mol L −1 KOH electrolyte at room temperature. Highlights: The Fe2 O3 /C catalyst for OER was prepared using a facile urea combustion method. The Fe2 O3 /C electrode showed excellent electrocatalytic ability towards OER. The particles were irregular spherical with 10–30 nm and dispersed uniformly.